2020
DOI: 10.1242/jeb.226076
|View full text |Cite
|
Sign up to set email alerts
|

A comparative perspective on lung and gill regeneration

Abstract: The ability to continuously grow and regenerate the gills throughout life is a remarkable property of fish and amphibians. Considering that gill regeneration was first described over one century ago, it is surprising that the underlying mechanisms of cell and tissue replacement in the gills remain poorly understood. By contrast, the mammalian lung is a largely quiescent organ in adults but is capable of facultative regeneration following injury. In the course of the past decade, it has been recognized that lun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 192 publications
0
22
0
Order By: Relevance
“…External respiratory structures, such as gills, are particularly prone to damage, but many animals can regenerate these structures [e.g. annelids, damselflies, fish, amphibians (Bely & Sikes, 2010 ; Brown & Emlet, 2020 ; Cadiz & Jonz, 2020 ; Drewes & Zoran, 1989 ; Eycleshvmer, 1906 ; Mierzwa et al ., 2020 ; Robinson et al ., 1991 b ; Saito et al ., 2019 ; Wells, 1952 )]. Siphons, which are used for pumping external water to the gills in bivalves and thus are important in respiratory function, can also often be regenerated (de Vlas, 1985 ; Meyer & Byers, 2005 ; Tomiyama, 2016 ).…”
Section: Effects Of Injury Across Levels Of Biological Organizationmentioning
confidence: 99%
“…External respiratory structures, such as gills, are particularly prone to damage, but many animals can regenerate these structures [e.g. annelids, damselflies, fish, amphibians (Bely & Sikes, 2010 ; Brown & Emlet, 2020 ; Cadiz & Jonz, 2020 ; Drewes & Zoran, 1989 ; Eycleshvmer, 1906 ; Mierzwa et al ., 2020 ; Robinson et al ., 1991 b ; Saito et al ., 2019 ; Wells, 1952 )]. Siphons, which are used for pumping external water to the gills in bivalves and thus are important in respiratory function, can also often be regenerated (de Vlas, 1985 ; Meyer & Byers, 2005 ; Tomiyama, 2016 ).…”
Section: Effects Of Injury Across Levels Of Biological Organizationmentioning
confidence: 99%
“…Despite these differences, the zebrafish equivalent of these structures still has the potential to provide immense insight into tumor-TME interactions. The gills like lungs are sites of oxygen exchange and contain many of the same cell types, including alveolar epithelial type I cells (called pavement cells in fish), goblet cells, and neuroepithelial cells ( Cadiz and Jonz, 2020 ). Both lungs and gills are also important sites of barrier immunity where zebrafish have been used to study the developmental origins of tissue-resident macrophages ( Lin et al, 2020 ) and also gill/lung regeneration ( Cadiz and Jonz, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The gills like lungs are sites of oxygen exchange and contain many of the same cell types, including alveolar epithelial type I cells (called pavement cells in fish), goblet cells, and neuroepithelial cells ( Cadiz and Jonz, 2020 ). Both lungs and gills are also important sites of barrier immunity where zebrafish have been used to study the developmental origins of tissue-resident macrophages ( Lin et al, 2020 ) and also gill/lung regeneration ( Cadiz and Jonz, 2020 ). Furthermore, the zebrafish has become a well-established model to investigate lymphangiogenesis and the HSC niche ( Flores et al, 2010 ; Wattrus and Zon, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although they do not possess lungs, several studies including our own, have recently highlighted the potential of the adult zebrafish (Danio rerio) as an alternative model system for respiratory tissue investigations of inflammation and repair [9][10][11][12]. In the adult zebrafish, the respiratory organs are the gills which are located in branchial chambers on each side of the head under the protection of a bony flap, the operculum.…”
Section: Introductionmentioning
confidence: 99%
“…They found that resected filaments are 50% complete after ~ 40 days and 85% complete after ~160 days. The mechanism of gill filament regeneration after resection is believed to involve the formation of a blastema [12]. While very informative, this injury model could be further enhanced by studies that recapitulate the extensive tissue damage seen in chronic lung diseases.…”
Section: Introductionmentioning
confidence: 99%